Disability, Education and Psychology: Psychological Dynamics in Individual Development and Education Process - Yildirimer, Kursat Sahin (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The relationship between disability, education, and psychology plays a crucial role in the academic, social, and emotional development of individuals. Disabled individuals face various challenges in education, such as low self-confidence, social isolation, learning difficulties, and peer bullying. An inclusive and supportive education system can enhance their academic success and psychological well-being. This study explores the psychological and pedagogical challenges faced by disabled individuals in education, focusing on issues such as lack of self-confidence, fear of failure, and social adaptation difficulties. Additionally, it examines the impact of inclusive education policies and psychological support programs, including cognitive-behavioral therapy, group therapy, and social support mechanisms, on the academic and psychosocial development of disabled students. The research adopts a qualitative approach, utilizing literature review and case analysis to assess the effectiveness of psychological support mechanisms in inclusive education. Findings suggest that strengthening these mechanisms and promoting inclusive policies contribute to the better integration of disabled individuals into society. The study highlights the need for collaboration between teachers, families, and policymakers to ensure equal educational opportunities. The results provide insights for developing strategies to enhance the participation and success of disabled individuals in education.